KENYAMANAN PERAWAT DALAM BERPENAMPILAN - Antia, Antia (Indonesian Journal of Nursing Health Science, 2016)
AbstractThe appearance is one part of the professional identity of nurses. This research aimed to identity comfort for nurses of the appearance. This research designed using a descriptive phenomenological, the data collected by Focus Group Discussion, participants selected by purposive sampling, data analysis using Giorgi methods, result of research themes: design and clothing material, facilities and the role of company. It could be conclude the comfort for nurses is important at the appearance. The managerâs role is very important in controlling the appearance.Â Keywords: appearance, comfort, nurse